Induction of Apoptosis and Growth-Inhibition by Thymoquinone in ACHN and GP-293 Cell Lines in Comparable with Cis-Platinum - Samira Shahraki; Reza Mohebbati; Mohammad Naser Shafei; Mahmoud Mahmoudi; Sara Hosseinian; Soghra Parhizgar; Zohreh Naji Ebrahimi Yazd; Nazanin Entezari Heravi; Reza Nejad Shahrokh Abadi; Abolfazl Khajavirad (Korean Pharmacopuncture Institute, 2019)
Objective:In the current work, we investigated the cytotoxic and apoptotic effects of Thymoquinone (TQ), an active compound of Nigella sativa (N. sativa) and Cis-platinum, on normal renal epithelial (GP-293) and human renal adenocarcinoma cell lines (ACHN).Methods:GP-293 and ACHN cell lines were cultured in Dulbecco's modified Eagle's medium (DMEM) with 10% Fetal bovine serum (FBS) and 1% penicillin plus streptomycin antibiotic. The MTT assay was used for cellular viability assessment. Viability of cells was observed using inverted light microscope 24, 48 and 72 h after exposure of the cells to various concentrations of TQ (1, 2.5, 5, 10, 50 and 100 µg/ml) and Cis-platinum (0.5, 1, 1.5, 2, 3, 6 and 12.5 µg/ml). Moreover, apoptosis was analyzed with a flow-cytometry method. The untreated cells were considered as control group.Results:Morphological changes such as reduced cell number and increased intercellular distance and reduced cell viability in ACHN and GP-293cell lines were observed in both TQ and Cis-platinum groups; however, Cis-platinum had greater effect on ACHN cell line than GP-293 cell line. In addition, GP-293 cell line was more sensitive to TQ compared to ACHN cell line. Furthermore, TQ and Cis-platinum had apoptotic effects on both ACHN and GP-293 cell lines.Conclusion:Our findings demonstrated that TQ and Cis-platinum had cytotoxic and apoptotic effects on both cell lines, However, GP-293 cell line was more sensitive to TQ. Additionally, Cis-platinum was more effective on ACHN cell line than on GP-293 cell line.